Old angel midnight - Kerouac, Jack, 1922-1969 (Open Road Integrated Media, 2016)
A sensory narrative poem capturing the rhythms of the universe and secrets of the subconscious with stunning linguistic dexterity from the author of On the Road A spontaneous writing project in the form of an extended prose poem, this sonorous and spiritually playful book is one of Jack Kerouac's most boldly experimental works. Collected from five notebooks dating from 1956 to 1959--a time in which Kerouac was immersed in Buddhist theory--Old Angel Midnight is comprised of sixty-seven short sections unified by an unwavering dedication to sounds, the subconscious, and verbal ingenuity. Friday Afternoon in the Universe, in all directions in & out you got your men women dogs children horses pones tics perts parts pans pools palls pails parturiences and petty Thieveries that turn into heavenly Buddha. Thus begins Kerouac's Joycean language dance. From birdsong to dharmic verse, street jargon to French slang, the resonances of the universe come blaring in though the windows, unfurling their meaning as the mind lets go and listens.